Porous Bioceramics use Albumin as a Pore-Forming Material - Fadli, Ahmad; Komalasari, Komalasari; Irdoni, Irdoni; Adiani, Wan Elsa Novtari (Chempublish Journal, 2023)
Porous bioceramics have been used in biomedical field, especially for bone implant. To generate pores in bioceramics, pore creating substances are added into the process of making ceramic bodies. The purpose of this study is to make porous bioceramics with tri calcium phosphate (TCP) raw material using albumin with variation in the amount of albumin in the raw material and drying temperature on the physical and chemical properties of TCP. Raw material slurry was made by mixing 7 g of TCP, 2 g of starch and 1.5 g of Darvan 821A with 5 g, 7 g and 9 g of albumin in a beaker glass while stirring at a rate of 150 rpm for 3 hours. The slurry was poured into a mold and heated in an oven at 180°C, 200°C and 220°C for 1 hour. Subsequently the sample was burned at 600˚C for 1 hour, following with sintering at 1.100°C for 2 hours. Bioceramic porosity is greater by increasing the amount of albumin and drying temperature, while the compressive strength decreases. Obtained TCP porosity is in the ranges of 68% -78% and compressive strength 0.14-1.4 MPa.